Labor Policy and Digital Technology Use : Indicative Evidence from Cross-Country Correlations - Packard, Truman G.; Montenegro, Claudio E. (World Bank, Washington, DC, 2017)
This paper exploits variation in country-level indicators drawn from published data to analyze the relationship between labor regulation and the use of digital technology. The analysis shows a statistically and economically significant association between digital technology use by firms and a country's statutory minimum wage and employment protection regulations. The results are robust to the inclusion of controls for level of development, economic stability, available infrastructure, and trade openness. To ensure the broadest country coverage, the paper develops new indexes of employment protection, using the World Bank's Doing Business indicators, which allow several aspects of labor market regulation—such as restrictions on hours and hiring, dismissal procedures, and severance costs--to be analyzed separately.